Mosquito larval habitats, meteorological factors, and alternatives for vector control in Makkah Al–Mukarramah, the Kingdom of Saudi Arabia - Haitham Badrawy; Khalid Hassan; Osman Ahmed; Rami Al-Sharif (Asian Pacific Journal of Tropical Medicine)
Objective: To characterize mosquito larval habitats and the influence of meteorological factors on their prevalence, and to suggest alternatives for vector control in Makkah Al-Mukarramah. Methods: A mosquito survey was conducted within the 16 municipalities of Makkah Al-Mukarramah, from November 2022 to October 2023. The characteristics of larval habitats used by all reported species as oviposition sites were determined. Seasonal house, container, and breteau indices were used to determine larval abundance. Results: 16 Species belonging to five genera [Aedes (3 spp.), Anopheles (3 spp.), Culex (8 spp.), Culiseta (1 sp.), and Lutzia (1 sp.)] were collected. A total of 185 608 potential mosquito larval habitats were surveyed. Of these, 95 853 (67.4%) were Aedes, 45 522 (32%) were Culex, 718 (0.5%) were Anopheles, and 38 (0.03%) were other species; 154 726 (83.4%) were water sources for mosquito larvae, and among these sources, 7 663 (5.0%) were positive for larvae, with 45.9% indoors and 54.1% outdoors. Most of the positive larval habitats were recorded in Al-Shawqiya (1 093, 14.3%), Al-Sharayia (1 003, 13.1%) and Al-Umrah (984, 12.8%). A total of 142131 mosquito larvae and pupae were collected. The majority number of positive residences for all mosquito larvae was observed in January 2023 (1 658, 21.6%). Conclusions: New appropriate alternatives for vector control are proposed, such as mechanical, biological, and environmental control.